Between Two Worlds: Exploring Identity in Last, First, Middle by Joseph Azam: A Cultural Hybridity Theory - Iezaz Ul Hassan; Zareena Qasim (Indus Journal of Social Sciences, 2025)
The research aims to investigate the theme of Identity in essay ‘Last, First, Middle’ by Joseph Azam from a postcolonial perspective, employing the theoretical framework of Homi K. Bhabha. By critically examining the experiences of a refugee grappling with notions of selfhood and belonging amidst the enduring colonial legacy, this study endeavors to shed light on the intricate process of identity negotiation. The overarching objective is to investigate the ways in which individuals in liminal spaces navigate the complex terrains of multiple cultural identities, while simultaneously interrogating the concepts of the Ambivalence, Third space, Hybridity, and Mimicry as articulated by Bhabha. Through an incisive analysis of the nuanced dynamics of identity formation, this research contributes to the broader understanding of postcolonial perspectives within the realm of literary analysis, thus enriching the discourse on cultural negotiation, diasporic experiences, and the intricacies of subjective constructions in postcolonial contexts.